A biomass based free radical scavenger binder endowing a compatible cathode interface for 5 V lithium-ion batteries. Issue 1 (22nd November 2018) - Ma, Yue; Chen, Kai; Ma, Jun; Xu, Gaojie; Dong, Shanmu; Chen, Bingbing; Li, Jiedong; Chen, Zheng; Zhou, Xinhong; Cui, Guanglei
Abstract : A lignin binder has been introduced to high voltage lithium-ion batteries to suppress electrolyte decomposition by scavenging free radicals. Abstract : 5 V lithium ion batteries (LIBs) are promising candidates for high energy density batteries. However, conventional carbonate-based liquid electrolyte is vulnerable to oxidative decomposition caused by free radical attack, which leads to poor cycling performance of the 5 V LIBs. Herein, we present a novel strategy based on the free radical scavenging effect to suppress the electrolyte decomposition of 5 V class batteries composed of LiNi0.5 Mn1.5 O4 (LNMO) cathodes and carbonate-based electrolyte. Our strategy is to scavenge the free radicals during the charging process at the cathode interface by adopting a renewable biomass lignin binder with numerous phenol groups, which can significantly suppress the free radical chain reaction and subsequently generate a compatible multi-dimensional interphase between the electrode and electrolyte. The lignin based electrode exhibited a capacity retention of 94.1% after 1000 cycles, which is significantly higher than that of its PVDF counterpart (46.2%). This work represents a milestone contribution to the strategy for resolving the interfacial issue of high voltage cathode materials, initiating a big step in boosting 5 V batteries.